Factors Influencing Workforce Development of TVET Graduates: A Case Study of Electrical Engineering Students in a TVET College in South Africa - Ntetha, Zameka; Taole, Matshidiso Joyce (Journal of Technical Education and Training, 2025)
Developing the workforce is integral to individual, community, and organisational economic development for current and future businesses and industries. This qualitative case study explored factors influencing the workforce development of Technical and Vocational Education and Training (TVET) college graduates. The research sample was drawn using purposive and convenience sampling. The data was collected through semi-structured interviews with ten participants (five Electrical Engineering students, two lecturers, one head of department, and two Human Resource managers). Thematic analyses were used to analyse data. The findings revealed that the TVET curriculum needs to be more responsive to the needs of the students. In addition, the study showed that the Electrical Engineering course lacks the practical component, and the course’s brief duration makes it impossible to finish the curriculum. This study recommends that the curriculum used in TVET colleges be revised continuously to ensure that students acquire the appropriate and relevant skills that will prepare them for employment. The practical component of the curriculum should be prioritised. Furthermore, a coordinated approach involving stakeholders (TVET colleges, industries, and students) should be followed to strengthen relationships and ensure that students are prepared to meet the demands of the labour market. If current TVET actors do not act, current TVET trends and practices could impact the local economy and the availability of skilled workers